2022
DOI: 10.1038/s41522-022-00270-7
|View full text |Cite
|
Sign up to set email alerts
|

Protease activities of vaginal Porphyromonas species disrupt coagulation and extracellular matrix in the cervicovaginal niche

Abstract: Porphyromonas asaccharolytica and Porphyromonas uenonis are common inhabitants of the vaginal microbiome, but their presence has been linked to adverse health outcomes for women, including bacterial vaginosis and preterm birth. However, little is known about the pathogenesis mechanisms of these bacteria. The related oral opportunistic pathogen, Porphyromonas gingivalis, is comparatively well-studied and known to secrete numerous extracellular matrix-targeting proteases. Among these are the gingipain family of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 138 publications
(172 reference statements)
0
13
0
Order By: Relevance
“…S. pyogenes expresses a highly conserved virulence factor streptopain (a C10 family cysteine peptidase) known to degrade an array of GAS and host proteins [ 44 ]. Although much of the work on this C10 cysteine protease has been reported from Streptococcal strains, many recent studies have identified this protease or its homologs in other bacterial species [ 34 , 35 , 45 , 46 ]. The biological activities and molecular functions of proteins can be predicted from their amino acid sequences [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. pyogenes expresses a highly conserved virulence factor streptopain (a C10 family cysteine peptidase) known to degrade an array of GAS and host proteins [ 44 ]. Although much of the work on this C10 cysteine protease has been reported from Streptococcal strains, many recent studies have identified this protease or its homologs in other bacterial species [ 34 , 35 , 45 , 46 ]. The biological activities and molecular functions of proteins can be predicted from their amino acid sequences [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…109 Proteases also have the potential to weaken cervical function and other host defences against sPTB. 110,111 Several host protease inhibitors (such as cystatin A, inter-alpha-trypsin inhibitor and serine protease inhibitor Kazal-type 5) were found to be associated with optimal Lactobacillus dominant microbiomes in a metaproteomics study. 112 One of the proteins identified in this study, cystatin A, was found to decrease towards the onset of labour in another study by Heng et al 113 Furthermore, secretory leukocyte protease inhibitor, which has a protective and anti-inflammatory role in the genital tract, 114 is decreased in women with STIs or BV 115 and has been found to be associated with lower risk of sPTB when present at high levels.…”
Section: Human Protein and Metabolite Biomarkers Of Sptbmentioning
confidence: 99%
“…There is recent evidence that human proteases, a broad group of enzymes that can modify protein products and function by breaking down polypeptides, 108 may increase the inflammatory response elicited by less‐optimal microbiota (such as L. iners ), which in turn could increase the risk of sPTB 109 . Proteases also have the potential to weaken cervical function and other host defences against sPTB 110,111 . Several host protease inhibitors (such as cystatin A, inter‐alpha‐trypsin inhibitor and serine protease inhibitor Kazal‐type 5) were found to be associated with optimal Lactobacillus dominant microbiomes in a metaproteomics study 112 .…”
Section: Introductionmentioning
confidence: 99%
“…This characterization of virulence activities in vaginal Porphyromonas species highlights their potential to alter the homeostasis of reproductive tissues and harm pregnancy through clotting disruption, fetal membrane weakening, and premature cervical remodeling. 48 In addition to its protective function, changes in the properties of the CMP have been linked to an elevated risk of preterm birth. 19 Therefore, understanding the intricate interplay between the lower reproductive tract microbiota, CMP, and mechanisms of infection ascent is crucial for unraveling the complex dynamics that contribute to preterm birth risk and developing potential preventive strategies.…”
Section: Immunological Function Of the Cervical Mucus Plugmentioning
confidence: 99%